Adaptive Capacity As a Form of Bureaucratic Reform in Enhancing Tax Services - Gita Susanti; Muhammad Irvan Nur Iva; Didik Iskandar (Jurnal Manajemen Pelayanan Publik, 2023)
Bureaucratic reform is the government's challenge in services to the community. The strategy that needs to be implemented by public organizations is to encourage adaptive capacity because of the massive public demand for convenience and quality services. This study aims to analyze and explore bureaucratic reform and the adaptive capacity of public organizations which act as leading sectors in tax services in Makassar City. This study applies qualitative methods through case studies strategy as an exploratory type. Information was obtained from stakeholders including local government, banking, the community and other stakeholders who actively contribute and are involved in the tax service process. The main data was obtained from interviews with informants, observing research objects and searching for related documents. Interactive analysis is the main analysis with activities of collecting data, reducing data, presenting data and drawing conclusions. The research results show that regional governments have realized bureaucratic reform and adaptive capacity in the form of strategies and innovations in digital-based tax services in order to encourage an increase in Regional Original Income. Adaptive capacity makes an important contribution in driving the success of the bureaucratic reform agenda but requires strengthening local regulations.